ANALISIS PENDAPATAN USAHA ROTI PADA INDUSTRI RUMAH TANGGA AISYAH BAKERY DI KOTA PALU - Pribadi, Andi; Alam, Max Nur; Effendy, Effendy (AGROTEKBIS, 2017)
This study aimed to analyze the income of household bread industry of Aisyah bakery       in palu. This research site was located at Mandala Street, North Birobuli, South Palu subdistrict     of Palu City, for two months starting from February to March 2017. Determination of respondents in this study was done purposively. The respondents were one leader of Aisyah Bakery Industry, and three employees of the Bakery Industry, so that the total number of the respondents was four people. The income of the bakery was analyzed using the income analysis. The total revenue generated by the bakery was IDR 35,100,000 with the total cost of IDR 24,503,269. Therefore,     the income of the bakery was IDR 10,596,731. Key Words: Aisha Bakery, household industry and income.